2012
DOI: 10.1038/srep00535
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin is an exogenous activator of 1,25D3-MARRS/Pdia3/ERp57 and improves Alzheimer's disease pathologies in 5XFAD mice

Abstract: The aim of this study was to investigate the effects and the mechanism of diosgenin, a famous plant-derived steroidal sapogenin, on memory deficits in Alzheimer's disease (AD) model mice. Diosgenin-treated 5XFAD mice exhibited significantly improved performance of object recognition memory. Diosgenin treatment significantly reduced amyloid plaques and neurofibrillary tangles in the cerebral cortex and hippocampus. Degenerated axons and presynaptic terminals that were only observed in regions closely associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(167 citation statements)
references
References 55 publications
7
156
2
2
Order By: Relevance
“…Recently, 1,25D3-membraneassociated, rapid response steroid-binding protein (1,25D3-MARRS) was identified as a target protein for Dio. Moreover, Tohda et al reported that Dio may function as an exogenous stimulator of 1,25D3-MARRS that induces axonal growth and regrowth of neurons (6). Hence, Dio may act on critical signaling pathways as a therapy for Alzheimer's disease.…”
mentioning
confidence: 99%
“…Recently, 1,25D3-membraneassociated, rapid response steroid-binding protein (1,25D3-MARRS) was identified as a target protein for Dio. Moreover, Tohda et al reported that Dio may function as an exogenous stimulator of 1,25D3-MARRS that induces axonal growth and regrowth of neurons (6). Hence, Dio may act on critical signaling pathways as a therapy for Alzheimer's disease.…”
mentioning
confidence: 99%
“…One such is diosgenin, a plant-derived steroidal sapogenin. Mice treated with diosgenin significantly reduced amyloid plaques and neurofibrillary tangles in the cerebral cortex and hippocampus 29 . More importantly, 1,25D₃-MARRS was shown to be a target of diosgenin and 1,25D₃-MARRS knockdown completely inhibited diosgenin-induced axonal growth in cortical neurons.…”
Section: Abbreviations Listmentioning
confidence: 99%
“…Steroids are lipophilic and thereby have the potential to interact with hydrophobic compounds (Manrique-Moreno et al, 2014). Liberation of diosgenin from its binding compounds is difficult because diosgenin binds to sugars (Rahu and Rao, 2012) and can interact with proteins (Tohda et al, 2012;Manivannan et al, 2013). Therefore, impurities in the crude extract of diosgenin may consist of complex compounds.…”
Section: Diosgenin Content Of Crude Extractmentioning
confidence: 99%